Control of magnetic ordering by Jahn--Teller distortions in Nd(2)GaMnO(6) and La(2)GaMnO(6). - Cussen, E; Rosseinsky, M; Battle, P; Burley, J; Spring, L; Vente, J; Blundell, S; Coldea, A; Singleton, J (2001)
The substitution of Ga(3+) into the Jahn--Teller distorted, antiferromagnetic perovskites LaMnO(3) and NdMnO(3) strongly affects both the crystal structures and resulting magnetic ordering. In both compounds the Ga(3+) and Mn(3+) cations are disordered over the six coordinate sites. La(2)GaMnO(6) is a ferromagnetic insulator (T(c) = 70 K); a moment per Mn cation of 2.08(5) mu(B) has been determined by neutron powder diffraction at 5 K. Bond length and displacement parameter data suggest Jahn--Teller distortions which are both coherent and incoherent with the Pnma space group symmetry of the perovskite structure (a = 5.51122(4) A, b = 7.80515(6) A, c = 5.52947(4) A) at room temperature. The coherent distortion is strongly suppressed in comparison with the parent LaMnO(3) phase, but the displacement ellipsoids suggest that incoherent distortions are significant and arise from local Jahn--Teller distortions. The preparation of the new phase Nd(2)GaMnO(6) has been found to depend on sample cooling rates, with detailed characterization necessary to ensure phase separation has been avoided. This compound also adopts the GdFeO(3)-type orthorhombically distorted perovskite structure (space group Pnma, a = 5.64876(1) A, b = 7.65212(2) A, c = 5.41943(1) A at room temperature). However, the B site substitution has a totally different effect on the Jahn--Teller distortion at the Mn(3+) centers. This phase exhibits a Q(2) mode Jahn--Teller distortion similar to that observed in LaMnO(3), although reduced in magnitude as a result of the introduction of Ga(3+) onto the B site. There is no evidence of a dynamic Jahn-Teller distortion. At 5 K a ferromagnetically ordered Nd(3+) moment of 1.06(6) mu(B) is aligned along the y-axis and a moment of 2.8(1) mu(B) per Mn(3+) is ordered in the xy plane making an angle of 29(2) degrees with the y-axis. The Mn(3+) moments couple ferromagnetically in the xz plane. However, along the y-axis the moments couple ferromagnetically while the x components are coupled antiferromagnetically. This results in a canted antiferromagnetic arrangement in which the dominant exchange is ferromagnetic. Nd(2)GaMnO(6) is paramagnetic above 40(5) K, with a paramagnetic moment and Weiss constant of 6.70(2) mu(B) and 45.9(4) K, respectively. An ordered moment of 6.08(3) mu(B) per Nd(2)GaMnO(6) formula unit was measured by magnetometry at 5 K in an applied magnetic field of 5 T.